The expression of Aldolase B in islets is negatively associated with insulin secretion in humans - Gerst, Felicia; Fleming, Thomas; Nawroth, Peter Paul (The journal of clinical endocrinology & metabolism, 2018)
Context: Reduced β-cell mass, impaired islet function, and dedifferentiation are considered causal to development of hyperglycemia and type 2 diabetes. In human cohort studies, changes of islet cell–specific expression patterns have been associated with diabetes but not directly with in vivo insulin secretion.Objective: This study investigates alterations of islet gene expression and corresponding gene variants in the context of in vivo glycemic traits from the same patients. Methods: Fasting blood was collected before surgery, and pancreatic tissue was frozen after resection from 18 patients undergoing pancreatectomy. Islet tissue was isolated by laser capture microdissection. Islet transcriptome was analyzed using microarray and quantitative RT-PCR. Proteins were examined by immunohistochemistry and western blotting. The association of gene variants with insulin secretion was investigated with oral glucose tolerance test (OGTT)-derived insulin secretion measured in a large cohort of subjects at increased risk of type 2 diabetes and with hyperglycemic clamp in a subset.Results: Differential gene expression between islets from normoglycemic and hyperglycemic patients was prominent for the glycolytic enzyme ALDOB and the obesity-associated gene FAIM2. The mRNA levels of both genes correlated negatively with insulin secretion and positively with HbA1c. Islets of hyperglycemic patients displayed increased ALDOB immunoreactivity in insulin-positive cells, whereas α- and δ-cells were negative. Exposure of isolated islets to hyperglycemia augmented ALDOB expression. The minor allele of the ALDOB variant rs550915 associated with significantly higher levels of C-peptide and insulin during OGTT and hyperglycemic clamp, respectively. Conclusion: Our analyses suggest that increased ALDOB expression in human islets is associated with lower insulin secretion.
Gesehen am 29.03.2019